Relationship Between Knowledge and Adherence on Taking Hypertension Medication - Aliyah, Nurul (jitek, 2025)
Hypertension is a chronic condition often called the “silent killer” due to asymptomatic nature and high risk of complications such as stroke, heart failure, and kidney disease when not properly managed. In Indonesia, adherence to antihypertensive medication remains suboptimal, with patient knowledge identified as a key influencing factor. This study aimed to examine the relationship between knowledge level and adherence to antihypertensive medication among patients at Public Health Center X Palembang. A cross-sectional design was employed involving 102 hypertension patients selected through purposive sampling. Data were collected using a structured, validated, and reliable questionnaire assessing knowledge related to hypertension and adherence behaviors using Cronbach alpha. Statistical analysis using the Chi-Square test showed a significant association between knowledge and adherence (p = 0.001), with an Odds Ratio (OR) of 7.091 (95% CI: 2.635–19.084), indicating that patients with good knowledge were over seven times more likely to adhere to medication compared to those with poor knowledge. Effective education improves not only awareness but also self-management skills, such as timely medication intake and handling of side effects. The results suggest that patient education should be a central strategy in primary care, particularly using accessible media like short videos and WhatsApp-based support to reach older populations.